2014
DOI: 10.1128/jcm.01606-13
|View full text |Cite
|
Sign up to set email alerts
|

High Nasal Burden of Methicillin-Resistant Staphylococcus aureus Increases Risk of Invasive Disease

Abstract: e In a retrospective cohort study of 1,140 patients harboring methicillin-resistant Staphylococcus aureus, the nasal burden was low in 31%, category 1؉ to 2؉ in 54%, and category 3؉ to 4؉ in 15%. There was a significant trend in infection risk with increasing nasal burden (P ‫؍‬ 0.007). In multivariate models, high nasal burden remained significantly associated with invasive infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The inoculum size used in this study was relatively low, but was geared to previous findings yielding mean MRSA nasal colonization densities of 794 CFU [63] and mean S. aureus colonization densities of 10 CFU for intermittent and 63 CFU for persistent carriers [64] , respectively. Thus, the inoculum size of this study corresponds to MRSA amounts in roughly one third of patients [65] . Therefore, a comparatively poor test sensitivity for some swab-types would be a minor issue for the majority of MRSA carriers, especially since test sensitivity can be boostered by including a broth culture incubation step [66] , [67] , [68] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inoculum size used in this study was relatively low, but was geared to previous findings yielding mean MRSA nasal colonization densities of 794 CFU [63] and mean S. aureus colonization densities of 10 CFU for intermittent and 63 CFU for persistent carriers [64] , respectively. Thus, the inoculum size of this study corresponds to MRSA amounts in roughly one third of patients [65] . Therefore, a comparatively poor test sensitivity for some swab-types would be a minor issue for the majority of MRSA carriers, especially since test sensitivity can be boostered by including a broth culture incubation step [66] , [67] , [68] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both broth culture and swabs with poor test sensitivity undermine quantification of MRSA amounts in nasal cavities. Yet, information on bacterial numbers is useful, since a high concentration of S. aureus in the nares is a risk factor for subsequent invasive infection [65] , [69] and is an independent risk factor for the development of a surgical site infection [70] .…”
Section: Discussionmentioning
confidence: 99%
“…However, and not surprisingly, neither of these methods could adequately discriminate between S. epidermidis isolates from infection and contaminant sources. This can be attributed to the finding that colonization often precedes infection, which renders a method based on MLST data unable to distinguish between hospital isolates that cause infections and those identified solely as contaminants (26,28).…”
mentioning
confidence: 99%
“…Rates of MRSA in CRS have been seen to be as high as 26% in 2010, with the trend of MRSA isolation increasing . Further, it has been noted that high nasal burden of MRSA is linked with an increased risk of developing invasive infection and is a reservoir for bacteraemia . Along with P128 in this study, phage‐derived proteins have also been found to be efficacious against MRSA CIs .…”
Section: Discussionmentioning
confidence: 99%